The impact of extensive reading on English language proficiency and motivation to read - Dhiraj Singh, Navinder Kaur (2015)
This study focuses on the development and implementation of an extensive reading (ER) programme to enhance English Language proficiency and motivation to read among fourteen-year old students in a secondary school in Malaysia. The nine-month study utilized an experimental design where the 120 participants were divided into two groups: an experimental group (59 students) and a control group (61 students). The experimental group was engaged in a weekly 40-minute scheduled class time where extensive reading was carried out in school while the control group read in their free time. Both groups were provided with the same reading materials. The effectiveness of the programme in developing three aspects of students’ language proficiency - vocabulary, general language proficiency and reading comprehension was measured using three instruments which were the vocabulary, cloze and comprehension tests. An affective questionnaire was designed to assess change in motivation to read and structured open-ended interviews were conducted on 20 students to elicit feedback on the effectiveness of the ER programme. Results from t-test paired-samples and independent samples showed that the experimental group improved in the vocabulary, cloze and reading comprehension tests while the control group did not show any improvement. However, there was no significant difference in motivation to read in both groups. The results suggest that monitored ER scheduled during a weekly class time where students read comprehensible articles should be made part of the curriculum. This can be achieved through the proposed Collaborative ER Model.